2020
DOI: 10.3390/pharmacy8020107
|View full text |Cite
|
Sign up to set email alerts
|

The Mbeya Antimicrobial Stewardship Team: Implementing Antimicrobial Stewardship at a Zonal-Level Hospital in Southern Tanzania

Abstract: Background: In 2017, Mbeya Zonal Referral Hospital (MZRH) and the University of South Carolina (UofSC) agreed to collaboratively strengthen antimicrobial prescribing in the southern highlands of Tanzania and train a new generation of clinicians in responsible antimicrobial use. Methods: Key stakeholders and participants were identified and the Mbeya Antimicrobial Stewardship Team (MAST) was created. The team identified assets brought by the collaborators, and four investigations of baseline needs were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Networks and communications were reported in eight studies as a facilitator [ 37 , 43 , 47 , 50 , 56 , 62 , 79 , 80 ]. Successful interventions were often developed and implemented by an experienced and well-coordinated team of local and international stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…Networks and communications were reported in eight studies as a facilitator [ 37 , 43 , 47 , 50 , 56 , 62 , 79 , 80 ]. Successful interventions were often developed and implemented by an experienced and well-coordinated team of local and international stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…There have been relatively few studies on community pharmacy and ADDO antibiotic provision in Tanzania, and these are limited geographically and dated [ 20 , 21 , 22 , 23 ]. A mystery client study in the urban area of Moshi (Kilimanjaro, northeast Tanzania) found 92% of community pharmacies provide antibiotics without prescription [ 24 ], and client exit interviews in urban Moshi found three-quarters of antibiotic purchases were made without prescription [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been demonstrated that acceptable quality bacteriology can be achieved in these settings when provided with adequate financial, logistic and supervisory support [ 3 ]. Availability of bacteriology testing is also key to implementation of antimicrobial stewardship programs in LMIC [ 13 , 14 ]. Antimicrobial stewardship, defined as the effort to promote appropriate use of antimicrobials to improve patient outcomes, reduce antibiotic resistance and decrease spread of multi-drug resistance [ 15 ], relies on knowledge of local AMR epidemiology to effectively guide clinicians towards appropriate treatments.…”
Section: Introductionmentioning
confidence: 99%